The Arbitration institutions and their role in determining the law applicable to investment contracts - a comparative study - Ali Muslim, - Assistant Lecturer Hassan (The college of law and political science journal, 2023)
act special a establish ,)25 (Article ,Law Civil the in and legislator Iraqi The parties the gives article this ,contracts international for base reference obligations contractual the to applicable law the choose to freedom the the ,choice implicit or explicit an of absence the In .implicitly or explicitly located is contractors the of domicile joint the which in State the of law in State the of law the ,differ they if and ,united is it if applied be shall .apply shall concluded is contract the which